Cyprus : First Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Cyprus' First Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. The program is on track, and ownership by the authorities has improved. Fiscal targets were met with a comfortable margin. All structural benchmarks were also observed, albeit some with a brief delay. The authorities have made important strides to complete the bank resolution process, publish a roadmap to gradually ease payment restrictions, and finalize a restructuring strategy for the cooperative credit sector. However, much remains to be done to fully implement the financial sector restructuring strategy and restore confidence in the system.